Percepción docente de estilos de liderazgo de directores de instituciones educativas de secundaria de la Red N° 1 Ventanilla - Montalvo Tacza, Nidia Ada (2012)
This study shows is the results of our investigation as in important style of leadership that many principal have. So many high schoolteacher from different schools of Ventanilla Ugel N°1, take in mind that if many principal ore able to manage correctly the the school that they were. Besides this simple study was based on the information that teachers found, about 206 teachers help in this resource from this jurisdiction. Furthermore teachers made a questionnaire. A questionnaire was used by Mr. Castro ; Mr. Nader and Mr. Casullo (2004) and was adaptable by Miss. Escandon; Miss. Montalvo; Miss. Tamaris in 2009, as a result this showed us 3 types of leadership, for instance transformational, transactional and Laisser Faire. the test allows us to get the punctuation, in each style and their respective magnitude Meanwhile the result that we got, told we that many teachers think that principals have the laissez fair style and and forme principals practice the transaccional leadership.